Mechanistic understanding of the charge storage processes in FeF2 aggregates assembled with cylindrical nanoparticles as a cathode material for lithium‐ion batteries by in situ magnetometry. Issue 6 (30th April 2022) - Hu, Zhengqiang; Zhang, Fengling; Liang, Huanyu; Zhang, Hao; Wang, Huaizhi; Wang, Tiansheng; Liu, Renbin; Liu, Jie; Li, Yadong; Dong, Xiaotong; Bao, Lianyu; Liang, Zhuan; et al.
Abstract: Transition metal fluorides (TMFs) cathode materials have shown extraordinary promises for electrochemical energy storage, but the understanding of their electrochemical reaction mechanisms is still a matter of debate due to the complicated and continuous changing in the battery internal environment. Here, we design a novel iron fluoride (FeF2 ) aggregate assembled with cylindrical nanoparticles as cathode material to build FeF2 lithium‐ion batteries (LIBs) and employ advanced in situ magnetometry to detect their intrinsic electronic structure during cycling in real time. The results show that FeF2 cannot be involved in complete conversion reactions when the FeF2 LIBs operate between the conventional voltage range of 1.0–4.0 V, and that the corresponding conversion ratio of FeF2 can be further estimated. Importantly, we first demonstrate that the spin‐polarized surface capacitance exists in the FeF2 cathode by monitoring the magnetic responses over various voltage ranges. The research presents an original and insightful method to examine the conversion mechanism of TMFs and significantly provides an important reference for the future artificial design of energy systems based on spin‐polarized surface capacitance. Abstract : In situ magnetometry was first employed to investigate the charge storage mechanism of FeF2 cathode, which clearly reveals that spin‐polarized surface capacitance and incomplete conversion occur when the battery operates between 1.0 and 4.0 V and the corresponding conversion ratio of FeF2 can be further estimated.